2005
DOI: 10.2174/0929867054367220
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives as 5HT1A Receptor Ligands-Past and Present

Abstract: Serotonin is a neuromediator, well-know for its implication in mood regulation, anxiety, depression and, insomnia as well as in normal human function such as sleep, sexual activity and appetite. In this way, serotonin (5-hydroxytryptamine, 5-HT) is one of the most attractive targets for medicinal chemists and pharmaceutical companies. Among 5-HTRs, the 5-HT1A subtype is the best studied, and it is generally accepted that it is involved in psychiatric disorders such as anxiety and depression. Several structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 112 publications
1
76
0
4
Order By: Relevance
“…The unsubstituted indolepropylphenylpiperazine (12a) showed a marked affinity for 5-HT 1A , which increased after the introduction of a methoxyl group in the ortho position (12b). This result agrees with a number of previous studies 11,14,[24][25][26] in which the 2-methoxyarylpiperazine derivative exhibited one of the highest affinities of the series.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The unsubstituted indolepropylphenylpiperazine (12a) showed a marked affinity for 5-HT 1A , which increased after the introduction of a methoxyl group in the ortho position (12b). This result agrees with a number of previous studies 11,14,[24][25][26] in which the 2-methoxyarylpiperazine derivative exhibited one of the highest affinities of the series.…”
Section: Resultssupporting
confidence: 93%
“…In general, the arylpiperazine moiety is a good template for drugs acting on many different biological targets, especially CNS receptors. [11][12][13] As a consequence, many compounds containing this scaffold bind with high affinity at 5-HT 1A receptors, but only a few of them also show high selectivity for 5-HT 1A over other receptors. 14) Structure-activity relationship (SAR) studies, performed with numerous generations of arylpiperazine derivatives, showed that CNS activity and both, receptor affinity and selectivity depend basically on the N-1-aryl substituent and a terminal fragment bound to the N-4 atom of the piperazine moiety by an alkyl chain.…”
mentioning
confidence: 99%
“…However, it could not be ruled out that subtle changes, beyond the detection limit of in vivo microdialysis coupled to HPLC detection could occur. Among the 14 subtypes of 5-HT receptors, the 5HT 2A and 5-HT 1A subtypes have been consistently found to be involved in mood regulation (Caliendo et al, 2005;Weisstaub et al, 2006). As shown in supplemental Figure S1 (available at www.jneurosci.org as supplemental material), 5-HT 2A binding sites in limbic areas and in the raphe are not altered following VGLUT3 deletion.…”
Section: Vglut3mentioning
confidence: 94%
“…A total of 259 5-HT 1A receptor ligands were collected from previous studies [1, , which are composed of 137 agonists and 122 antagonists with diverse structural classes such as aminotetralins, indolylalkylamines, ergolines, aporphines, arylpiperazines and aryloxyalkylamines (Tables S1 and S2 in Supplementary Information). Because we aimed to build a binary classifier, the partial agonists of the 5-HT 1A receptor were classified as agonists.…”
Section: Data Setsmentioning
confidence: 99%